Acercamiento a la tradición poética peruana: características y series en la poesía del siglo XX - Castillo Castillo, Wendy María (2020)
A category such as tradition is a functional and important part of the History of Literature, since it is the means by which it is possible to examine the development of a literature through time, from its formation to the identification of its heyday. and maturity. Moreover, it is not only limited to the literature of a country or continent, it implies a diachronic approach towards the materials that participate in the discursive construction, literary species, genres, topics, themes mainly articulated in the discourses. In this sense, when dealing with the poetic tradition, the close and temporal knowledge of the process of poetry is appealed to, which allows us to know its constant characteristics, of which the modelling plays a significant functional role (Maestro, 2014). Thus, the materialities of language are examined in a selection of poetic corpus belonging to the 20th century, gradually and chronologically to emphasize the role of evolution.